Viral load levels measured at set-point have risen over the last decade of the HIV epidemic in the Netherlands. - Luuk Gras; Suzanne Jurriaans; Margreet Bakker; Ard van Sighem; Daniela Bezemer; Christophe Fraser; Joep Lange; Jan M Prins; Ben Berkhout; Frank de Wolf; ATHENA National Observational Cohort Study (PLoS ONE)
Background HIV-1 RNA plasma concentration at viral set-point is associated not only with disease outcome but also with the transmission dynamics of HIV-1. We investigated whether plasma HIV-1 RNA concentration and CD4 cell count at viral set-point have changed over time in the HIV epidemic in the Netherlands. Methodology/principal findings We selected 906 therapy-naïve patients with at least one plasma HIV-1 RNA concentration measured 9 to 27 months after estimated seroconversion. Changes in HIV-1 RNA and CD4 cell count at viral set-point over time were analysed using linear regression models. The ATHENA national observational cohort contributed all patients who seroconverted in or after 1996; the Amsterdam Cohort Studies (ACS) contributed seroconverters before 1996. The mean of the first HIV-1 RNA concentration measured 9-27 months after seroconversion was 4.30 log(10) copies/ml (95% CI 4.17-4.42) for seroconverters from 1984 through 1995 (n = 163); 4.27 (4.16-4.37) for seroconverters 1996-2002 (n = 232), and 4.59 (4.52-4.66) for seroconverters 2003-2007 (n = 511). Compared to patients seroconverting between 2003-2007, the adjusted mean HIV-1 RNA concentration at set-point was 0.28 log(10) copies/ml (95% CI 0.16-0.40; p<0.0001) and 0.26 (0.11-0.41; p = 0.0006) lower for those seroconverting between 1996-2002 and 1984-1995, respectively. Results were robust regardless of type of HIV-1 RNA assay, HIV-1 subtype, and interval between measurement and seroconversion. CD4 cell count at viral set-point declined over calendar time at approximately 5 cells/mm(3)/year. Conclusion The HIV-1 RNA plasma concentration at viral set-point has increased over the last decade of the HIV epidemic in the Netherlands. This is accompanied by a decreasing CD4 cell count over the period 1984-2007 and may have implications for both the course of the HIV infection and the epidemic.